A arte e a brincadeira e suas interfaces com a dramatização em psicologia comunitária: um estudo de processos de mediação simbólica - Pinheiro, Francisco Pablo Huascar Aragão (2008)
This work has the purpose of investigate how occur the process of symbolic mediation through the use of dramatization techniques in Community Psichology’s interventions, having the will to comprehend and theoretically articulate the dramatization technique with related questions to art and play. The theoric bases are found in the Cultural-Historical theory for the comprehension of the psychical unctioning and the psychological mediated process. The empiric study was fulfilled in the context of a Community Psichology’s intervention situation with a group of teenagers from a NGO at Fortaleza, being analyzed only one meeting in which the dramatization technique has been worked with and the topic of the debate was “adolescence”. The intervention situation choosed for analysis was registered in video, specifically the dramatized activity, acknowledging that in it’s different stages, the initial debate phase (warming), the dramatization itself and the later moment of reflexion generated by the dramatization. The analysis proceeding was handed as interpretative-construtive, in a way that was realized a contend analysis with the intent to produce clues that allowed to trace links of of intelligibility on the studied phenomena. Observing that the question in the analyzed meeting was the way how the teenagers of the group conceived and qualified the characteristics and papers captured as relevant to “teenager”, two analysis categories were elected: “Social Knowledge” and “Moral Judgment”. The analysis results point to the constructions allowed by the dramatization and are considered in the possible articulations between the art, the play, and the psychical functioning. In this sense, the dramatization situation can constitute a mediated process, in so far as translate and objectifies not only an individual experience, but also says about a living per passed by the history of the place and the social interactions made, and also opens space for the re-elaboration of the experience as creator act. In the same time, the dramatization can be comprehended as an imagination act, so as it is conceived the play in a cultural-historical vision, meaning that it isn’t conceived as an isolated symbolic act, but it is linked to the imagination, that, just as the others psychical functions, is originated by the action. Therefore, the imagination is captured as the toy without action and composes the scenery of dramatization.